2012
DOI: 10.5902/198050985080
|View full text |Cite
|
Sign up to set email alerts
|

Óleo essencial de <i>Eucalyptus grandis</i> Hill ex Maiden no estímulo à micorrização de mudas de sibipiruna (<i>Caesalpinia peltophoroides </i>Benth.)

Abstract: RESUMOOs metabólitos secundários extraídos de espécies florestais formadoras de ectomicorrizas podem estimular a simbiose entre fungos ectomicorrízicos e espécies florestais nativas do Rio Grande do Sul. O objetivo deste trabalho foi determinar o efeito do óleo essencial de eucalipto na formação de associação ectomicorrízica e no crescimento de mudas de sibipiruna, em condições de casa de vegetação. Plântulas de sibipiruna foram submetidas a quatro tratamentos constituídos pela presença e ausência do inóculo e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…These results corroborate with Steffen et al (2012), who observed that the application of Eucalyptus grandis essential oil at a concentration of 40 µL . L -1 stimulated the occurrence of ectomycorrhizal association of Pisolithus microcarpus in Caesalpinia peltophoroides Benth.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…These results corroborate with Steffen et al (2012), who observed that the application of Eucalyptus grandis essential oil at a concentration of 40 µL . L -1 stimulated the occurrence of ectomycorrhizal association of Pisolithus microcarpus in Caesalpinia peltophoroides Benth.…”
Section: Resultssupporting
confidence: 91%
“…the secondary metabolism of the eucalyptus essential oil: Eucalyptol, p-Cymeno, Spathulenol, Lepidozenal, Cubeb-11-ene, Junenol and 4(15)-Dehydroglobulol (STEFFEN et al, 2013) in the substrate contributed to the association between the fungus and the plant due to the occurrence of biochemical signaling (STEFFEN et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Estudos têm demostrado que os fungos ectomicorrízicos são beneficiados pela presença de óleo essencial de Eucalyptus grandis quando submetidos a metais pesados (STEFFEN et al, 2011), a aplicação do óleo é bioestimulante do crescimento vegetativo de mudas de eucalipto (STEFFEN; ANTONIOLLI; STEFFEN, 2010) e o óleo contribui para a formação de ectomicorriza em mudas de sibipiruna (Caesalpinia peltophoroides Benth.) (STEFFEN et al, 2012). Nas espécies arbóreas nativas como a timbaúva-preta (Enterolobium contortisiliquum Vell.)…”
Section: Introductionunclassified